Incidences of School-based Anti-gay and Gender- related Bullying: Differences across Levels of Education - Evan McEwing; Joseph M. Zolobczuk; Kiet D. Huynh; Ariel A. Gonzalez; Debbiesiu L. Lee (University of North Florida, 2018)
Anti-gay and gender-related bullying and harassment are pervasive public health problems found in schools and are correlated with negative mental health and educational outcomes for students. This study examines the differences in the forms and prevalence of anti-gay and gender-related bullying with students from middle school, secondary, and post-secondary institutions. This information can assist researchers and practitioners in better understanding the prevalence of anti-gay verbal versus physical harassment at particular education levels. The sample comprised 7,007 participants. Multivariate analysis of variance was used to examine differences across levels of education, race/ethnicity, and gender on the 9-item Gender and Orientation Attitudes Scale. We found that middle school students were least comfortable with others perceived as gay or transgender and least likely to speak up against anti-gay bullying. Both middle school and high school students were most likely to use anti-gay and gender-related verbal slurs. Middle school students reported the greatest prevalence of physical harassment towards peers based on perceived gender and orientation. Implications of these results for public health are discussed.